We need psychologists! Paediatr Child Health - van den Heuvel, M (Paediatr Child Health, 2016)
Paediatricians are more likely than ever to encounter patients with mental health problems on a daily basis. There is a need for investment in proven treatments, such as psychology-based interventions, for children identified with mental health disorders. There are four main arguments supporting the engagement of psychologists for children with mental health problems: there is clear evidence that psychological interventions can effectively treat a wide range of mental health disorders; many parents and children are more open to exploring psychological therapies rather than medication for mental health problems; psychologists are trained and licensed to perform psychoeducational assessments, which can provide invaluable information about a child’s learning profile, attention problems and overall intelligence; and behaviour problems in children can be prevented or improved through parent-based interventions. The authors’ strongly advocate for the public funding of psychology services – both in collaborative primary care models and in the school setting.